2011
DOI: 10.1111/j.1439-0264.2011.01113.x
|View full text |Cite
|
Sign up to set email alerts
|

NADPH‐d‐Positive Mast Cells in the Canine Paranal Sinus

Abstract: This study aimed to investigate the enzyme histochemical expression of NADPH-d in mast cells in the wall of the paranal sinus in male and female dogs. NADPH-d-positive cells with weak, medium and strong enzyme histochemical expression were observed in the stroma of the sinus near the blood vessels of the microcirculatory bed and around the apocrine and sebaceous glands. In the same areas, mast cells with similar dimensions and morphology were demonstrated by metachromasia on paraffin and cryostat cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Therefore, the L. minor addition has a beneficial effect on BLM-induced inflammation and fibrotic processes, possibly participating in the Th1/Th2 immune response modulation and the subsequent decrease in the MCs and eosinophils set. Our results are supported by reports from a number of authors on the crucial role of mast cells and the Th2 immune response in IPF progression [16][17][18][21][22][23]69]. The accumulation of collagen together with increased MCs number in the interalveolar septa in BLM treated group detected in the current study correlates with the findings of several authors suggested that the MCs mediators tryptase, chymase and histamine induce lung fibroblast proliferation and collagen production [23,[70][71][72][73] recently demonstrated that stretch-induced degranulating MCs activate the pro-fibrotic cytokine TGF-β1.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, the L. minor addition has a beneficial effect on BLM-induced inflammation and fibrotic processes, possibly participating in the Th1/Th2 immune response modulation and the subsequent decrease in the MCs and eosinophils set. Our results are supported by reports from a number of authors on the crucial role of mast cells and the Th2 immune response in IPF progression [16][17][18][21][22][23]69]. The accumulation of collagen together with increased MCs number in the interalveolar septa in BLM treated group detected in the current study correlates with the findings of several authors suggested that the MCs mediators tryptase, chymase and histamine induce lung fibroblast proliferation and collagen production [23,[70][71][72][73] recently demonstrated that stretch-induced degranulating MCs activate the pro-fibrotic cytokine TGF-β1.…”
Section: Discussionsupporting
confidence: 90%
“…It is well-known that lung MCs synthesize mediators involved in the contraction of airway and lung smooth muscle cells, such as serotonin and ghrelin [16]. Inhibitory non-adrenergic non-cholinergic airway smooth muscle response is mediated by nitric oxide (NO) [17], and mast cells are a secondary source of NO-dependent relaxation of smooth muscle cells [18,19]. MCs accumulation in the lungs of patients with various forms of pulmonary fibrosis has been reported in a number of studies [20][21][22].…”
Section: Introductionmentioning
confidence: 99%